2019
DOI: 10.1080/14737175.2020.1708195
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive agents in Alzheimer’s disease: beyond vascular protection

Abstract: Introduction: Midlife hypertension has been consistently linked with increased risk of cognitive decline and Alzheimer's disease (AD). Observational studies and randomized trials show that the use of antihypertensive therapy is associated with a lesser incidence or prevalence of cognitive impairment and dementia. However, whether antihypertensive agents specifically target the pathological process of AD remains elusive. Areas covered: This review of literature provides an update on the clinical and preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 148 publications
(200 reference statements)
0
31
1
2
Order By: Relevance
“…Finally, an observational study showed that ACEIs increase the risk of mortality in AD patients (Kehoe et al, 2013). However, this finding was not replicated in other cohorts (Lebouvier et al, 2020).…”
Section: Studies Showing Neutral or Negative Effects On Cognition Andmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, an observational study showed that ACEIs increase the risk of mortality in AD patients (Kehoe et al, 2013). However, this finding was not replicated in other cohorts (Lebouvier et al, 2020).…”
Section: Studies Showing Neutral or Negative Effects On Cognition Andmentioning
confidence: 94%
“…DRIs directly inhibit generation of Ang I from angiotensinogen, acting upstream of both ARBs and ACEIs (Riccioni, 2013). RAS inhibitors can reduce Aβ deposition and its consequences, and also suppress inflammation, oxidative stress, vascular damage/ischemia, and increase acetylcholine release and glutamate uptake (Gebre et al, 2018;Lebouvier et al, 2020). Especially, ARBs can prevent impairment of the BBB and reduce infiltration of inflammatory mediators observed in many neurodegenerative disease such as AD (Gebre et al, 2018).…”
Section: Renin-angiotensin System-acting Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently a novel angiotensin receptor/neprilysin inhibitor (ARNI) sacubitril/valsartan has been approved for treatment of hypertension and prevention of heart failure in elderly hypertensive patients (for review see Kario, 2018 ). While there is no doubt that hypertension should be treated for prevention of cardiovascular diseases as well as of stroke and vascular dementia, the role of NEP inhibitors as antihypertensive agents in AD pathogenesis remains unclear and needs further investigation ( Lebouvier et al, 2020 ).…”
Section: Role Of Nep In Diseasesmentioning
confidence: 99%
“…One RCT found bene cial cerebrovascular effects of calcium antagonists on AD [31].However, one recent MR analysis have showed that lowering SBP via AHMs is unlikely to affect the risk of developing AD, and if speci c AHM classes do reduce the risk of AD, the mechanism may not be via SBP pathway [10]. Actually, studies have pointed out that some drugs, such as those acting through angiotensin receptor and calcium channel blocking mechanisms, have protective effects on AD, independently of BP lowering [32]. For example, the intracellular buildup of calcium in neurons can be neurotoxic and thus CCB might result in neuroprotection [33].…”
Section: Discussionmentioning
confidence: 99%